Recording and Reporting Database Design of Patients with Multidrugs Resistance Organisms - Arsyad, Mualif (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
-